Synthesis and characterization of organic – inorganic hybrid catalysts (polyoxometalates- MCM 41/F or PCH/F) for use in oxidation of organosulfur compounds (Revista de Investigaciones Universidad del Quindío, 2013)
This work studied the synthesis and characterization of organic-inorganic hybrid catalysts used in the oxidation of organosulfur compounds. The synthesis was carried out using by treating a siliceous material with an aminosilane agent in order to obtain appropriate surface for the adsorption of heteropolyoxoanions (HPOMs) Anderson type [MMo6O24H6]3- with M= Co (III) and Rh (III) and a structural derivate, [Co2Mo10H4O38]6-. The characterization of the modified and impregnated materials was carried out by XRD, CHNO-S, SEM-EDS, atomic absorption (AAS) and SBET. The analysis by physicochemical techniques revealed an interaction the surface interaction with Mo = O groups (active catalytic sites). The unmodified supports SBET were 1000 and 500m2/g, which decreased after modification and impregnation. XRD verified the typical structural features of MCM 41 and PCH modified and impregnated. CHNO-S and SEM-EDS showed the presence of N due to the functionalizing. AAS showed a concentration between 8 and 14 % of adsorbed Mo from HPOM’s. The activity was correlated with presence of noble metal in the system containing Rh (III) and the different structural symmetry in Co2Mo10 system distorted, which its higher catalytic activity is associated to the active sites availability. The catalytic conversions were between 90 y 100% and selectivity to sulfone after 2h.
Keywords: desulfurization; hybrid catalysts; heteropolyoxoanions